(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2001)
A rich deposit of mammals was discovered in September 1995 at Poggio Rosso, the hill-top of the Matassino clay pit, in the Upper Valdarno Basin, 30 m above another deposit whose local fauna was assembled 30 years earlier. This latter provided the Matassino Locality, assigned to the beginning of the late Villafranchian Mammal Neogene age on the basis of its affinity with the Olivola faunal unit, which was also taken to represent the earliest assemblage in the Pleistocene. The paleomagnetic record in the short section across the Matassino Locality revealed the Olduvai chron, which was imprinted also in the fossil-bearing stratum of Poggio Rosso, so constraining both their ages to the latest Pliocene. The Poggio Rosso fauna, yet to be paleontologically determined, and the other late Villafranchian faunas collected in the Upper Valdarno from the Montevarchi complex fit a similar time span. Therefore, their magnetostratigraphically calibrated ages provide the time constraints for the biochronological relationships between faunas which can be tuned to several tie points for numerically evaluating their diversification steps during the whole Olduvai chron and shortly out of it.